2017
DOI: 10.18632/oncotarget.17884
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic microRNAs in upper tract urothelial carcinoma: multicenter and international validation study

Abstract: ObjectiveTo validate previously discovered miRNAs (miR-31-5p and miR-149-5p) as prognostic factors for UTUC in an independent cohort of UTUC patients.Patients and MethodsMulticenter, international and retrospective study of formalin-fixed paraffin-embedded tissue samples from 103 UTUC patients (45 progressing and 58 non-progressing) who underwent radical nephroureterectomy. Total RNA was isolated and reverse transcribed. The expression of target miRNAs (miR-31-5p and miR-149-5p) and the endogenous control miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The pathogenesis and prognosis of many cancers has implicated the deregulation of miRNAs, which play vital roles in regulating the expression of coding genes involved in a wide range of biological processes [14, 15]. Therefore, several studies have investigated the clinical value of miRNAs for the prediction of cancer outcomes [9, 16, 17]. Koolivand et al observed that miR-155 might function as an oncomir in AML and can be a prognosis biomarker for AML [18], while Xu H et al have reported role for miR-135a in predicting poor prognosis in AML [19].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis and prognosis of many cancers has implicated the deregulation of miRNAs, which play vital roles in regulating the expression of coding genes involved in a wide range of biological processes [14, 15]. Therefore, several studies have investigated the clinical value of miRNAs for the prediction of cancer outcomes [9, 16, 17]. Koolivand et al observed that miR-155 might function as an oncomir in AML and can be a prognosis biomarker for AML [18], while Xu H et al have reported role for miR-135a in predicting poor prognosis in AML [19].…”
Section: Discussionmentioning
confidence: 99%
“…Our group has prior experience in miRNA analysis from different types of urothelial cell carcinoma samples. On the one hand, we provided evidence that miRNAs can be used as prognostic biomarkers in UTUC in tissue samples [ 3 , 4 ]. On the other, we showed that miRNAs can be useful diagnostic and prognostic biomarkers for bladder cancer in urine samples [ 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In UTUC, miRNAs that play a major role in tumor progression and cancer-specific survival were identified as regulators of gene expression, including oncogene and tumor suppressor genes. Signalling pathways modified by prognostic markers have been recognized as being involved in UTUC progression ( Izquierdo et al, 2017 ). The regulatory roles of miRNAs in cell growth, apoptosis, autophagy, and aging have also been implicated ( Sohn, 2018 ).…”
Section: Introductionmentioning
confidence: 99%